Analysis of Teachers’ Pedgogic Competence in Elementary Schools - Rizki Ananda; Nadila Putri; Lusy Anggraini; Irvan Aditya (Edumaspul: Jurnal Pendidikan, 2023)
The teacher's pedagogic competence is a very important aspect of learning in schools because the teacher is the person who is responsible for preparing and implementing learning for students. Therefore, this research is very important to do, especially to evaluate whether elementary school teachers have sufficient pedagogical competence. This study aims to analyze the pedagogic competence of teachers in elementary schools using the developed assessment instrument. The method used in this study is a quantitative descriptive method, involving 50 teachers from elementary schools in certain areas. The instrument for assessing teacher pedagogic competence used in this study includes four aspects, namely lesson planning, learning implementation, learning evaluation, and professional development. The collected data were then analyzed using descriptive statistical techniques. The results of the study show that the majority of teachers in elementary schools have good pedagogical competence. However, several aspects still need to be improved, especially in planning lessons that are more structured and systematic and the ability to provide effective feedback on student learning outcomes. Therefore, it is suggested that teachers develop themselves through training and professional development to improve their pedagogic competence.